Long-term neuropeptide modulation of female sexual drive via the TRP channel in Drosophila melanogaster. - Kim, D.H.; Jang, Y.H.; Yun, M.; Lee, K.M.; Kim, Y.J. (Proceedings of the National Academy of Sciences of the United States of America, 2024)
Connectomics research has made it more feasible to explore how neural circuits can generate multiple outputs. Female sexual drive provides a good model for understanding reversible, long-term functional changes in motivational circuits. After emerging, female flies avoid male courtship, but they become sexually receptive over 2 d. Mating causes females to reject further mating for several days. Here, we report that pC1 neurons, which process male courtship and regulate copulation behavior, exhibit increased CREB (cAMP response element binding protein) activity during sexual maturation and decreased CREB activity after mating. This increased CREB activity requires the neuropeptide Dh44 (Diuretic hormone 44) and its receptors. A subset of the pC1 neurons secretes Dh44, which stimulates CREB activity and increases expression of the TRP channel Pyrexia (Pyx) in more pC1 neurons. This, in turn, increases pC1 excitability and sexual drive. Mating suppresses pyx expression and pC1 excitability. Dh44 is orthologous to the conserved corticotrophin-releasing hormone family, suggesting similar roles in other species.